2009
DOI: 10.2298/jas0903213p
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of yield and grain yield components of winter wheat varieties

Abstract: Mean positive correlation (r = 0,47**) between grain yield and number of plants per m² and strong correlation between grain yield and number of spikes per m² were established (r = 0,55**). Weak correlation was established between grain yield and productive tillering (r = 0,24**). Strong positive correlation (r = 0,51**) is between the number of spikes per m² and productive tillering, as well as between the number of plants per m² and number of spikes per m² (r = 0,68**). Very weak negative correlation (r = -0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The highest SN of genotypes Gyrmyzy gul1 and 12 nd FAWWON№97 could be due to high tillering capacity. Positive significant correlation of SN with GY was in agreement with GARCIA DEL MORAL et al (2003) and PROTIC et al, (2009). SL is a desirable trait under rain-fed condition, positively correlated with GY.…”
Section: Resultssupporting
confidence: 73%
“…The highest SN of genotypes Gyrmyzy gul1 and 12 nd FAWWON№97 could be due to high tillering capacity. Positive significant correlation of SN with GY was in agreement with GARCIA DEL MORAL et al (2003) and PROTIC et al, (2009). SL is a desirable trait under rain-fed condition, positively correlated with GY.…”
Section: Resultssupporting
confidence: 73%
“…Yield of wheat depended mostly on spikelet number, grain number, and 1,000 seed weight. Other investigations show, however, that the yield of wheat may be to a greater extent formed by the number of spike, number of grain and 1,000 seed weight (Protić et al, 2009;Rymuza et al, 2012). The applied method of PCA made it possible to fully assess the relations among wheat traits which are used for the analysis of observed diversity in regard to different traits.…”
Section: Resultsmentioning
confidence: 97%
“…It is clear that both of the first two factors which would express the combined effect of stem diameter, leaf width, tiller number, spike length, floret number, spikelet number, grain number, grain diameter, grain length, 1,000 seed weight were most closely associated with grain yield. Grain yield of bread wheat may be regarded as being composed of the components such as heads per plant, spikelets per spike, grains per spike and the 1,000 seed weight (Leilah and Al-Khateeb, 2005;Protić et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, for the selection of high yielding wheat varieties, 1000 kernel is often used as it is closely related to grain yield [40]. Protić et al [41] concluded that components such as heads per plant, spikelets per spike, grains per spike and the 1000 kernel weight can be considered part of grain yield of bread wheat. Besides, the fact that 1000 kernel weight and test weight are components of yield means these traits can be used to determine yields of flour and in the milling industry as major quality determinants [42].…”
Section: Principal Component Analysis For Nine Agronomical and Quality Traits In Six Different Environmental Conditionsmentioning
confidence: 99%